Role of Tajo Dance in The Bohien Dohik Ritual on Dayak Hibun in Parindu - Dewi, Della Aprilya; Tindarika, Regaria; Aditya, Mega Cantik Putri (Jurnal Pendidikan Sosiologi dan Humaniora, 2025)
This study examines the central role of the Tajo Dance in the Bohien Dohik healing ritual performed by the Dayak Hibun community in Parindu District, Sanggau Regency, West Kalimantan. The Tajo Dance is understood as a spiritual medium that connects humans, ancestors, and Penompo (God), and serves as an essential element in restoring balance between the physical world and the spiritual realm. This study aims to describe the role of the Tajo Dance in the Bohien Dohik healing ritual. The research method used is descriptive qualitative with an ethnocoreological and anthropological approach through observation, interviews, and documentation. The results show that the Tajo Dance, which is performed only at the highest levels of the ritual (levels 5, 6, and 7), functions as a medium to persuade the Minu (spirit) to return to the patient’s body, while also acting as a means of negotiation and reconciliation with spiritual entities. Through forty-four sequences of ancestral games, this dance presents symbolic elements of movement, costume, and ritual structure that reflect the spiritual journey of the Bohien. Overall, the Tajo Dance is not merely a form of artistic expression, but a core component that affirms cultural identity, strengthens social solidarity, and sustains the traditional healing system of the Dayak Hibun community. This study provides an important contribution to understanding local wisdom and the urgency of preserving ritual arts rooted in customary traditions.